Optimasi Biaya Pendistribusian Tempe Dengan Menggunakan Metode Stepping Stone Berbasis Android - Jeperson Hutahaean; William Ramdhan; Putri Rahma Dhini (STMIK Budi Darma, 2023)
In the era of globalization, the progress of science and technology is very rapidly developing. This progress contains several aspects of human life both in terms of education, daily activities and business activities. One of the businesses engaged in selling tempeh in the form of a home industry needs to utilize the maximum technology that is wrong using Android. This is done to help increase the number of customers, customer loyalty and more importantly compared to the minimum cost. One technology that can increase the number of customers, customer loyalty and more importantly compared to the minimum Android technology. Before carrying out the calculation process, the authors conducted research by observation and interview. Optimization is a method used to analyze a system based on research. The Stepping Stone method is used to calculate the minimum operational costs required when given resources. Is the main step of the Stepping Stone method using the North West Corner method. The principle of work and support is to allocate resources offered by home industries at minimum cost. After using this method, the result is Rp. 40,600 from the initial cost before minimization of Rp. 65,000.